Genetically encoded biosensors in plants: pathways to discovery - Walia, Ankit; Waadt, Rainer; Jones, Alexander M. (Annual review of plant biology, 2018)
Genetically encoded biosensors that directly interact with a molecule of interest were first introduced more than 20 years ago with fusion proteins that served as fluorescent indicators for calcium ions. Since then, the technology has matured into a diverse array of biosensors that have been deployed to improve our spatiotemporal understanding of molecules whose dynamics have profound influence on plant physiology and development. In this review, we address several types of biosensors with a focus on genetically encoded calcium indicators, which are now the most diverse and advanced group of biosensors. We then consider the discoveries in plant biology made by using biosensors for calcium, pH, reactive oxygen species, redox conditions, primary metabolites, phytohormones, and nutrients. These discoveries were dependent on the engineering, characterization, and optimization required to develop a successful biosensor; they were also dependent on the methodological developments required to express, detect, and analyze the readout of such biosensors.